Validation of Altered Umbilical Cord Blood MicroRNA Expression in Neonatal Hypoxic-Ischemic Encephalopathy - O’Sullivan, Marc Paul (JAMA Neurol, 2018)
IMPORTANCE: Neonatal hypoxic-ischemic encephalopathy (HIE) remains a significant cause of neurologic disability. Identifying infants suitable for therapeutic hypothermia (TH) within a narrow therapeutic time is difficult. No single robust biochemical marker is available to clinicians. OBJECTIVE: To assess the ability of a panel of candidate microRNA (miRNA) to evaluate the development and severity of encephalopathy following perinatal asphyxia (PA). DESIGN, SETTING, AND PARTICIPANTS: This validation study included 2 cohorts. For the discovery cohort, full-term infants with PA were enrolled at birth to the Biomarkers in Hypoxic-Ischemic Encephalopathy (BiHiVE1) study (2009-2011) in Cork, Ireland. Encephalopathy grade was defined using early electroencephalogram and Sarnat score (n = 68). The BiHiVE1 cohort also enrolled healthy control infants (n = 22). For the validation cohort, the BiHiVE2 multicenter study (2013-2015), based in Cork, Ireland (7500 live births per annum), and Karolinska Huddinge, Sweden (4400 live births per annum), recruited infants with PA along with healthy control infants to validate findings from BiHiVE1 using identical recruitment criteria (n = 80). The experimental design was formulated prior to recruitment, and analysis was conducted from June 2016 to March 2017. MAIN OUTCOMES AND MEASURES: Alterations in umbilical cord whole-blood miRNA expression. RESULTS: From 170 neonates, 160 were included in the final analysis. The BiHiVE1 cohort included 87 infants (21 control infants, 39 infants with PA, and 27 infants with HIE), and BiHiVE2 included 73 infants (control [n = 22], PA [n = 26], and HIE [n = 25]). The BiHiVE1 and BiHiVE2 had a median age of 40 weeks (interquartile range [IQR], 39-41 weeks) and 40 weeks (IQR, 39-41 weeks), respectively, and included 56 boys and 31 girls and 45 boys and 28 girls, respectively. In BiHiVE1, 12 candidate miRNAs were identified, and 7 of these miRNAs were chosen for validation in BiHiVE2. The BiHiVE2 cohort showed consistent alteration of 3 miRNAs; miR-374a-5p was decreased in infants diagnosed as having HIE compared with healthy control infants (median relative quantification, 0.38; IQR, 0.17-0.77 vs 0.95; IQR, 0.68-1.19; P = .009), miR-376c-3p was decreased in infants with PA compared with healthy control infants (median, 0.42; IQR, 0.21-0.61 vs 0.90; IQR, 0.70-1.30; P = .004), and mir-181b-5p was decreased in infants eligible for TH (median, 0.27; IQR, 0.14-1.41) vs 1.18; IQR, 0.70-2.05; P = .02). CONCLUSIONS AND RELEVANCE: Altered miRNA expression was detected in umbilical cord blood of neonates with PA and HIE. These miRNA could assist diagnostic markers for early detection of HIE and PA at birth.